Depressive symptoms among patients with schizophrenia in acute and remission phases - Peljto, Amir; Pešić, Danilo; Christodoulou, Nikos G; Lečić Toševski, Dušica (Vojnosanitetski pregled, 2020)
Bacground/Aim. Researchers suggest that among people with schizophrenia, the prevalence of depressive symptoms ranges from 7% to 80%. The rate of depressive symptoms among people with schizophrenia varies widely because of the phase of the disease, type of study applied, rating scale for depressive symptoms and diagnostic criteria. The aim of this research was to determine the prevalence of depressive symptoms and the clinical correlation of depressive symptoms with other clinical parameters (type and severity of psychotic symptoms, severity of illness, insight and global functioning) among patients with schizophrenia in acute and remission phases. Methods. This prospective clinical study enrolled 100 consecutive patients with schizophrenia both in acute and remission phases. Psychometric assessments were made using the Positive and Negative Syndrome Scale (PANSS) for rating the symptoms of schizophrenia, Scale to Assess the Unawareness of Mental Disorder (SUMD), Calgary Depression Scale for Schizophrenia (CDSS), and Global Assessment of Functioning Scale. Results. The prevalence of depressive symptoms among patients with schizophrenia in the acute phase was 23% at the study group, while in the remission phase it was 13%. In the acute phase, the CDSS scale correlated with a depressive and positive subscale of the PANSS scale as well as SUMD scale. In the remission phase, the CDSS scale correlated only with a depressive subscale of the PANSS scale. The CDSS scale did not correlate with the negative subscale of the PANSS scale. The subjective nature of depressive symptoms is more pronounced in the remission phase. Conclusion. Our findings showed that depressive symptoms were more pronounced in the acute psychotic phase than in the remission phase of schizophrenia. Targeted, patient oriented, and algorithm-based approach for treatment management, with taking into account different phenotypic expressions of the disorder (patients with and without affective symptoms) is warranted in patients with schizophrenia.